INOVASI PEMBELAJARAN DENGAN DICE BOARD GETS SMART DAMPAKNYA TERHADAP PROSES DAN KEMAMPUAN PEMECAHAN MASALAH - Alfan Efendi Ardiansah; Dr. Lisa Virdinarti Putra, S.Pd., M.Pd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem addressed in this study is the low ability of students to solve mathematics problems based on Higher Order Thinking Skills (HOTS) that involve problem-solving indicators. Based on a preliminary study, students at SDN Sidomulyo 04 showed difficulties in understanding the steps to solve problems due to a lack of understanding of problem-solving strategies. This indicates that their ability to identify and determine solutions has not been optimally developed. These difficulties are further supported by the researcher’s observations during the learning process, which revealed that students are not yet accustomed to applying critical and systematic thinking in solving mathematical problems. This study aims to examine the effect of the problem-solving learning model assisted by the Dice Board Gets Smart media on students’ problem-solving abilities. The main issue is the low problem-solving ability of students during the learning process. This research uses a quantitative approach with the population being all students at SDN Sidomulyo 04, while the sample consists of students from classes IIIA and IIIB. The results of the study show that: (1) There is a significant difference between the experimental class using the problem-solving model assisted by Dice Board Gets Smart media and the control class using the problem-solving model without the media, with a significance value of 0.012 < 0.05 based on the independent t-test. (2) There is an influence of the problem-solving learning model assisted by Dice Board Gets Smart media on students' problem-solving abilities, with a significance value of 0.001 < 0.05 based on the regression test. In conclusion, the problem-solving learning model assisted by the Dice Board Gets Smart media is effective in improving students’ problem-solving skills.